Perkembangan Kerajaan Allah di Zaman Petrus - Devita Septania; Wulan Darri; Sarmauli Sarmauli (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to examine and understand more deeply how the Kingdom of God developed during Peter's time, as well as its relevance for the lives of believers today. The approach used in this research is a descriptive qualitative approach with a library research method. Data collection techniques are carried out through the identification and selection of relevant literature, followed by a process of recording, grouping, and reviewing the content (content analysis). The data obtained are analyzed by comparing various sources to find correspondences, differences, and patterns of thought related to the development of the Kingdom of God. The results of the study analysis found the understanding that: (1) The Kingdom of God basically refers to the active government of God as King, not to a geographical area. This concept is rooted in the Old Testament and is the core of Jesus' message. The Kingdom of God has two complementary dimensions, namely the present reality that has been experienced by believers and the future reality that will be perfectly fulfilled at the end of time; (2) the development of the Kingdom of God in Peter's time is marked by the use of the "keys of the Kingdom" given to him by Jesus. Through three important events, namely Pentecost, the preaching in Samaria, and the Cornelius incident, Peter opened the way for Jews, Samaritans, and non-Jews to enter the Kingdom of God. This shows that God's salvation is universal and transcends ethnic boundaries; and (3) Peter's preaching established a new identity for God's people as "a chosen nation, a royal priesthood, a holy nation, God's own people." This identity has consequences for believers to live under God's rule and be His witnesses in the world, while waiting for the new heaven and new earth where righteousness resides.